Self-Concept in Music Video “Child” By Mark Lee: A Semiotic Analysis - Haryati, Haryati; Putriutami, Citra Yuke; Prichatin, Prichatin (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
The aims of this study were to describe the self concept and sign meaning in Mark Lee’s music video “Child.” The data sources obtained by the writer came from visual clips and textual data in the “Child” music video. The method applied in this study used a descriptive qualitative approach to describe and analyse the data. The results show the signs present the self-concept; each has different perspective of self concept. The researchers revealed the types pf self consept consisting of 12 self-esteem, 13 self-image, and 5 ideal selves. It can be concluded that the music video displays distinctive meaning and self-concept in both the visual and textual. Moreover, music video “Child” had 30 pieces of data that demonstrated the meaning of denotation, connotation, and myth. The entire semiotic meaning of the music video “Child” was about life during adolescence and their problems. This is demonstrated by the property, setting, and lighting found in this music video, which emphasises adolescence.